Evidence for asymmetric frontal-lobe involvement in episodic memory from functional magnetic resonance imaging and patients with unilateral frontal-lobe excisions. - Lee, A; Robbins, T; Smith, S; Calvert, G; Tracey, I; Matthews, P; Owen, A (2002)
Recently, there has been considerable debate regarding the involvement of the left and right prefrontal cortices in the encoding and retrieval of episodic memory. In a previous PET study, we found that the use of easily verbalisable material may lead to activation predominantly in the left lateral frontal cortex whilst the use of non-easily verbalisable material may lead to activation predominantly in the right lateral frontal cortex, in both cases irrespective of encoding and retrieval processes. In order to replicate and extend these findings, the same task was modified for use with fMRI. Six healthy volunteers were scanned while encoding and then recalling stimuli that either emphasised visual or verbal processes. It was found that, in comparison to a baseline condition, the encoding of visual stimuli led to a bilateral activation of the prefrontal cortex whilst the encoding of verbal stimuli led to a preferential activation of the left prefrontal cortex. An effect of stimulus type was less evident during retrieval, with both visual and verbal stimuli leading to bilateral prefrontal cortex activation. Overall, encoding and retrieval activated similar regions of the prefrontal cortex suggesting that these areas mediate processes that are fundamental to both aspects of memory. To extend these findings further, the tasks used in the fMRI study were used to assess a group of patients with unilateral frontal lesions and a group of healthy control volunteers. The patients were significantly impaired compared to the healthy volunteers, although no significant differences were found in performance between the right- and left-sided lesioned patients. This result suggests that the memory-related asymmetries observed during functional neuroimaging studies may not be critical for task performance.